Moral values of organization based on business moral patterns and legal requirements for presenting model in tax administration - Mehni, Yousef (2020)
The purpose of this research was to analyze and explain the organization's ethical values ​​based on ethical business models and legal requirements to present a model to the Kerman Tax Administration (Iran). The present investigation is descriptive and exploratory, and of a combined type (quantitative, qualitative). Therefore, the orientation of this research was first to determine and identify the components of the organization's ethical values, in addition to reviewing the literature and the research background. The exploratory qualitative sampling method and the sample size due to access limitations are considered for this stage 11 people. This group includes managers and employees of the Kerman Tax Administration. According to statistics, there are 727 managers and employees of the Kerman Tax Administration. Because the type of research requires information from specific individuals, that is, specific types of people such as managers (19) and employees (708) who can provide the desired information in the research, they were selected as a statistical sample. The validity of the questionnaire was confirmed by exploratory and confirmatory factor analysis and the reliability of the questionnaire was confirmed by Cronbach's alpha. In this research, ethical values ​​include organizational justice, organizational commitment, corporate moral culture, and social responsibility of an organization. Patterns of work morale include professional morale, social morale, and individual morale, and legal requirements include appropriate services, quality of services, and trust. In the case of the ethical values ​​measurement model based on ethical standards and legal requirements in the Kerman province, the correlation between variables is not more than 0.9. Therefore, there is no need to merge or remove them. Furthermore, all factor loads are greater than 0.5, indicating that all dimensions have good factor validity. Regarding the structural model of ethical values ​​based on ethical patterns and legal requirements in the tax administration of the Kerman province, the relationship between the variable of organizational ethical models and the corporate moral values ​​is positive and significant. There is also a positive and significant relationship between the variable of legal requirements and the ethical values ​​of the organization.